2011
DOI: 10.1080/17457300.2010.540334
|View full text |Cite
|
Sign up to set email alerts
|

Measuring risky adolescent cycling behaviour

Abstract: Adolescents are at a greater risk of being involved in traffic accidents than most other age groups, even before they start driving cars. This article aims to determine the factor structure of a self-report questionnaire measuring adolescent risky cycling behaviour, the ACBQ (Adolescent Cycling Behaviour Questionnaire). The questionnaire's structure was based on the widely used Driver Behaviour Questionnaire (DBQ). A sample of secondary school students (N = 1749; age range: 13-18 years) filled out the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
2
26
5
1
Order By: Relevance
“…Specifically, it is worth remarking on the associations reported between age of cyclists and road crash rates in the last 5 years which were in accordance with other empirical sources [35,36], i.e., cyclists with less age tend to accumulate higher crash rates (regardless of severity) when riding compared with those with a higher age/riding experience. Furthermore, age was also correlated with risk-related perceptions (linked to infrastructural and interactional factors) and risky behaviours on the road.…”
Section: Discussionsupporting
confidence: 59%
“…Specifically, it is worth remarking on the associations reported between age of cyclists and road crash rates in the last 5 years which were in accordance with other empirical sources [35,36], i.e., cyclists with less age tend to accumulate higher crash rates (regardless of severity) when riding compared with those with a higher age/riding experience. Furthermore, age was also correlated with risk-related perceptions (linked to infrastructural and interactional factors) and risky behaviours on the road.…”
Section: Discussionsupporting
confidence: 59%
“…Further, only two studies investigated the association between risk behaviour types and self-reported crashes. The study amongst a large sample of Dutch cyclists found a positive association with self-reported crashes (Feenstra et al, 2011), whereas the study amongst Dutch moped riders did not find such an association, possibly due to a smaller sample size (Steg & Van Brussel, 2009). Thus, in these studies the factor structure as well as the association with self-reported crashes differ from those found in studies on car drivers.…”
Section: Introductionmentioning
confidence: 95%
“…Table 1 presents an overview of the results of the four studies, showing that: (a) the expected 'violations' versus 'errors' factor structure was not found in some studies (Elliott & Baughan, 2004;Sullman & Mann, 2009), (b) the risk behaviour factors were highly intercorrelated (Feenstra, Ruiter, Schepers, & Kok, 2011;Steg & Van Brussel, 2009), and (c) in addition to 'errors' and 'violations' three other types of risk behaviour could be distinguished: 'dangerous play', 'lack of protective behaviour', and 'unsafe crossing' (Elliott & Baughan, 2004;Sullman & Mann, 2009). Further, only two studies investigated the association between risk behaviour types and self-reported crashes.…”
Section: Introductionmentioning
confidence: 96%
“…Así, existen adaptaciones para ciclistas (Feenstra, Ruiter, Schepers, Peters y Kok, 2011), para motoristas (Elliot, Baughan y Sexton, 2007) y, la más actual, para ambientes laborales (Newman y Von Schckmann, 2012). En consecuencia, el modelo de comportamiento de riesgo en conductores de Reason et al (1990) tiene un potencial enorme para su aplicación al estudio del comportamiento peatonal, ya que permite objetivar, medir y describir sistemáticamente, transgresiones, errores y lapsus al transitar por la ciudad.…”
Section: Introductionunclassified